A Changed Terrain for Popular Struggle - Magno, Alexander R. (Kasarinlan: Philippine Journal of Third World Studies, 2008)
There are numerous debates over the appropriate strategy now going on among the increasingly marginalized movements of the Filipino Left. The combined effects of political insignificance and deep internal disagreements are expressed in the increasing parochialization of left-wing discourse. Much passion has been invested in the fine doctrinal disagreements without addressing the contours of the larger reality - the huge structural, demographic, technological, and institutional changes sweeping the field of radical politics itself. As left wing forces become more preoccupied with disagreeing with each other, they lose touch of the larger constituencies and the broad social forces emerging in Philippine society today. More than the matter of strategy that preoccupies many Left-wing activists in the Philippines today, the crucial matter that ought to be addressed concerns the articulation of a progressive, credible social agenda for the future. This essay does not attempt to reach a resolution of the questions pertaining to the aforementioned that progressive and democratic movements in the Philippines and the rest of Southeast Asia must collectively deal with. At best, it attempts to construct these questions more adequately.